Scoping report for a farmer-herder conflict case study in Sudan - Sulieman, Hussein; Abdal Karem, S.M. (International Livestock Research Institute, 2023)
This scoping report combines findings from a scoping visit to the case study location with a review of the literature that describes salient features of the political economy in Sudan. The purpose of this report is to document findings as a contribution to and as preparation for fieldwork on farmer-herder conflicts. The report is produced by the CGIAR Research Initiative on Fragility, Conflict and Migration and the project Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC).